2013 PALYNOLOGY: THE BRIDGE BETWEEN PALAEOECOLOGY AND ECOLOGY FOR THE UNDERSTANDING OF HUMAN-INDUCED GLOBAL CHANGES IN THE MEDITERRANEAN AREA - Mercuri, A. M.; Marignani, M.; Sadori, L. (Annali di Botanica, 2013)
Editorial to Notes